The impact of environmental regulation on technological innovation of enterprises: Based on empirical evidences of the implementation of pollution charges in China - Yuxing Wang; Wenhui Ye; Bichun Wang (Economics: The Open-Access, Open-Assessment Journal, 2024)
Environmental protection is closely related to high-quality economic developments. Based on the matching of micro-databases from 2000 to 2008, this study used the "Regulations on the Collection and Use of Pollution Fees" policy implemented in China in 2003 as the exogenous impact to construct the intensity Difference in Differences model in order to investigate the effects of pollutant discharge fee on technological innovation of enterprises and the underlying mechanisms. The results showed that governmental environmental regulations significantly improved the level of technological innovation of enterprises, and the conclusion was still valid after a series of robustness tests. The results of the parallel trend verified the rationality of the differential setting and the dynamic effects showed that the pollutant discharge fees had a continuous promoting effect on the technological innovation of enterprises. The results of the placebo tests rejected the original hypothesis of the mistaken model. The mechanism verifications revealed that the strengthening of environmental regulation by the government acted on the innovation level of enterprises through the two mechanisms, i.e., the promotion of enterprises' fixed asset investments and government subsidies, and finally improved the enterprises' technological innovation levels.
Keywords: 330; environmental protection regulation; enterprise innovation; pollutant discharge fees; differences-in-differences